Amplified impact of contact uniformity on the performance of low-catalyst-loading fuel cells - Yuanzhe Ma; Xuanyu Wang; Ziliang Deng; Yongzhen Wang; Nanfeng Zheng; Kai Han; Zipeng Zhao (Energy Conversion and Management: X)
Reducing platinum group metal (PGM) usage in a proton exchange membrane fuel cell (PEMFC) is essential for its broad implementation. To ensure the performance of low-PGM-loading PEMFCs, the contact between the flow-field plates and the membrane electrode assembly (MEA) is critical. We found the MEA with lower catalyst loading is more sensitive to the change of contact uniformity, which can be quantified as average contact pressure and proportion of contact area. When the contact pressure distribution becomes less uniform and the average contact pressure between the flow-field ridge and MEA decreases from 1.05 to 0.15 MPa, the MEAs with the PGM loading of 0.100 mg/cm2 and 0.060 mg/cm2 exhibit 7.8 % and 37.8 % power drop at 2.0 A/cm2, respectively. The experimental data is consistent with the theoretical study and can be explained as lower catalyst loading comes along with a lower volume fraction of conductive carbon support and fewer platinum sites, making the electrochemical reaction’s ohmic and mass transfer overpotential more sensitive to the environmental change. More specifically, the theoretical study shows that the MEA with lower loading (0.04 mgPGM/cm2) suffers a more than doubled ohmic overpotential increase compared to the MEA with higher loading (0.12 mgPGM/cm2) when average contact pressure reduces from 0.8 MPa to 0.2 MPa. Also, the lower catalyst loading MEA faces four times more mass transfer overpotential increase when the proportion of contact area reduces from 100 % to 40 %. Our findings suggest that the requirement of mechanical design and manufacturing accuracy of the components should be higher for PEMFC with lower catalyst loading.